Integrating Multimedia for Strategic Da’wah Communication in the Digital Era - Mutiatun Nasihah; Farid Munfaati; Nadira Azzahra; Siti Akmalia Nada (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
The digital era requires people to be able to utilize multimedia technology in various ways, one of which is in terms of Islamic preaching. Using a descriptive qualitative method with a case study approach, this study aims to explore the process and impact of integrating multimedia for strategic da'wah communication employed by Sabilurrosyad Islamic Boarding School, Malang. Meanwhile, the data was collected through interviews, observation, and documentation to capture detailed insights and ensure a comprehensive understanding of the topic. The results of this study indicated that Sabilurrosyad Islamic Boarding School has implemented multimedia to disseminate Islamic content as a medium of da'wah on several digital platforms, including the Website, YouTube, Instagram, Facebook, X, and TikTok. To support the use of multimedia, Sabilurrosyad Islamic Boarding School formed an organization called Gasek Multimedia, which is responsible for creating and disseminating da'wah content on the official digital platform of the boarding school. Integrating multimedia for da’wah communication benefits society by providing accessible Islamic content and promoting goodness through engaging, efficient, and effective digital outreach. The findings of this study provide valuable insights into the importance of integrating multimedia for strategic da'wah communication in today's digital era. Keywords: Multimedia; Da’wah Communication; Digital Era